Physical and sexual victimization of persons with severe mental illness seeking care in central and southwestern Uganda - Mpango, Richard Stephen; Ssembajjwe, Wilber; Rukundo, Godfrey Zari; Amanyire, Philip; Birungi, Carol; Kalungi, Allan; Rutakumwa, Rwamahe; Tusiime, Christine; Gadow, Kenneth D.; Patel, Vikram; Nyirenda, Moffat; Kinyanda, Eugene (Frontiers in Public Health, 2023)
Purpose This study established the prevalence of physical and sexual victimization, associated factors and psychosocial consequences of victimization among 1,201 out-patients with severe mental illness at Butabika and Masaka hospitals in Uganda. Methods Participants completed structured, standardized and locally translated instruments. Physical and sexual victimization was assessed using the modified adverse life events module of the European Para-suicide Interview Schedule. We used logistic regression to determine the association between victimization, the associated factors and psychosocial consequences. Results The prevalence of physical abuse was 34.1% and that of sexual victimization was 21.9%. The age group of > = 50 years (aOR 1.02;95% CI 0.62–1.66; p = 0.048) was more likely to have suffered physical victimization, while living in a rural area was protective against physical (aOR 0.59; 95% CI 0.46–0.76; p = <0.001) and sexual (aOR 0.48, 95% CI 0.35–0.65; p < 0.001) victimization. High socioeconomic status (SES) (aOR 0.56; 95% CI 0.34–0.92; p = <0.001) was protective against physical victimization. Females were more likely to have been sexually victimized (aOR 3.38; 95% CI 2.47–4.64; p = <0.001), while being a Muslim (aOR 0.60; 95% CI 0.39–0.90; p = 0.045) was protective against sexual victimization. Risky sexual behavior was a negative outcome associated with physical (aOR 2.19; 95% CI 1.66–2.90; p = <0.001) and sexual (aOR 3.09; 95% CI 2.25–4.23; p < 0.001) victimization. Mental health stigma was a negative outcome associated with physical (aOR 1.03; 95% CI 1.01–1.05; p < 0.001) and sexual (aOR 1.03; 95% CI 1.01–1.05; p = 0.002) victimization. Poor adherence to oral anti-psychotic medications was a negative outcome associated with physical (aOR 1.51; 95% CI 1.13–2.00; p = 0.006) and sexual (aOR 1.39; 95% CI 0.99–1.94; p = 0.044) victimization. Conclusion There is a high burden of physical and sexual victimization among people with SMI in central Uganda. There is need to put in place and evaluate complex interventions for improving detection and response to abusive experiences within mental health services. Public health practitioners, policymakers, and legislators should act to protect the health and rights of people with SMI in resource poor settings.